Optical and RBS studies in Tm implanted ZnO samples - Monteiro, T.
We report on optical and structural analysis of Tm implanted ZnO [0001] single crystals. The samples were implanted at room temperature with 150 keV Tm+ ions with a nominal fluence of 5×1016 Tm +/cm2 and subsequently air annealed for 30 min at 800°C, 900°C and 950°C. The implantation damage and annealing effects were investigated with Rutherford Backscattering/Channelling Spectroscopy. We observe that following implantation the majority of Tm ions are incorporated on Zn sites. The optical properties of as-implanted and annealed samples have been studied by low temperature photoluminescence measurements. Well defined Tm-related near infrared emission were observed upon above band gap excitation and the data are consistent with the presence of multi Tm-related optical centers.